Position Of The Deed Of Will Made By Notary In Dispute Between The Heirs (Case Study Of Religion Court Decision No. 0427/Pdt.G/2014/PA.bla) - Nurul Kusumawati; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
An inheritor can make a deed of will before a Notary, so that in a dispute occur later on between the heirs, the deed of will can be used as a basis for deciding the dispute between parties. Notaries who have the authority to make a deed of will have the obligation to serve the community in making a deed of will in the form of an authentic deed as stipulated in Article 15 paragraph (1) of Law Number 2 year 2014 concerning Amendments to Law Number 30 on the Position of Notary, which reads